Pengaruh Pendidikan Keuangan Di Keluarga Dan Teman Sebaya Terhadap Perencanaan Keuangan Pribadi - Farhan Rizqullah, Muhammad; Andayani, Sari (GEMA EKONOMI, 2023)
The purpose of this study was to test and prove the effect of financial education in family and peers on personal financial planning. This research applies a "quantitative approach". The information collected in this study used "primary data" collected through questionnaires and disseminated through social media. The sample in this study used "S1 Students of the Faculty of Business Economics class of 2019 to 2022 UPN "Veteran" East Java". Sample selection using the proportionate stratified random sampling method. The test tool in this study is to use SPSS version 26. The results of this study show that financial education in the family has a significant effect on personal financial planning, while peers have no significant effect on personal financial planning.